Ex vitro propagation and phytochemical analysis of Serapias vomeracea (Burm.f.) Briq.: contribution to the conservation of Orchidaceae species - Çolak, Esin; Aytar, Erdi C.; Kömpe, Yasemin Ö. (Spanish Journal of Agricultural Research, 2024)
Aim of study: The primary objective of this study was to investigate the seed germination and antioxidant propertiesof Serapias vomeracea (Burm.f.) Briq. Specifically, the aims of the research were to explore the influence of the Tulasnellaceae spp, fungal isolate SVL-30 (MK250656), on germination and seedling development, compare antioxidant activity to that of ascorbic acid, analyse the phytochemical composition, and identify bioactive compounds present in the methanol extract. Area of study: University of Ondokuz Mayıs, Faculty of Sciences, Department of Biology, Samsun, Türkiye. Materials and methods: Pots containing S. vomeracea and SVL-30 fungus, along with a control group without fungus, were utilized for the experiment. The impact of the fungus on germination stages and seedling development was assessed. Antioxidant analysis involved determining phenolic and flavonoid content, as well as DPPH radical scavenging activity (IC50: 2.09 mg/mL). Chlorophyll and carotenoid contents were measured to evaluate the physiological health of the plant. GC-MS analysis was employed to identify 19 bioactive compounds present in the methanol extract. Main results: The fungus significantly stimulated germination, with 83.02% of seeds germinating, and 52.66% progressing to the seedling stage. Antioxidant analysis revealed substantial phenolic and flavonoid content in S. vomeracea seedlings, demonstrating potent antioxidant properties comparable to ascorbic acid. Chlorophyll and carotenoid contents emphasized the balanced and healthy physiology of the plant. GC-MS analysis identified 19 bioactive compounds in the methanol extract, highlighting the potential bioactivity of S. vomeracea. Research highlights: This study furnishes valuable information on the germination, phytochemical composition, and antioxidant capacity of S. vomeracea seedlings. The research underscores the potential bioactivity of the plant, substantiated by the identification of bioactive compounds. The findings lay the groundwork for further exploration of the potential health benefits of S. vomeracea. A strategic shift towards studies emphasizing sustainable agricultural practices is recommended, aiming to balance both conservation and utilization objectives.